Reinforcement of Maja Labo Dahu (shame and fear) attitude in practicing pancasila value through the learning of pancasila and civic education in State Madrasah Tsanawiyah (MTSN) 1 Bima city - Irawan, Bambang; Kusdarini, Eny (ScienceRise. Pedagogical education (Online), 2021)
This type of research is descriptive research by qualitative approach about the reinforcement of maja labo dahu attitude in practicing Pancasila value through the learning of Pancasila and civic education in MTsN 1 Bima City.  The technique of determining the subject research used purposive sampling with the source of data is 1) teacher of Pancasila and civic education, 2) student representatives, 3) curriculum representative, 4) coach of extracurricular activity, 5) principal and, 6) students. Data collection is conducted by observation, documentation and interview. The test validity is conducted by triangulation technique. The data analysis is analyzed by the technique of qualitative descriptive analysis. The research founding indicated that: first, the reinforcement of maja labo dahu attitude in practicing Pancasila values in MTsN 1 Bima City can be done by several ways, such as: a) verbally, by giving the understanding the meaning about the important of maja labo dahu philosophy toward students, b) exemplary, teacher can show a positive behaviour and attitude, for instance: courtesy, honesty, discipline, and appearance that can be imitated by students, and c) Habituation of religious attitudes, politeness, mutual respect and tolerance. Second, supporting factor of reinforcement maja labo dahu attitude in practicing Pancasila values through the learning of Pancasila and civic education in MTsN 1 Bima City for supporting factor, including: a) a competence teacher, b) facility, c) curriculum, d) extracurricular activity, e) school culture, f) parents and society, g) the involvement of all the teacher and school staff. Meanwhile, obstacle factor, including: a) the curriculum content has been not listed explicitly the philosophy of maja labo dahu, b) the large school environment, c) school environment, family and society do not support each other. However, the solution is the reinforcement of maja labo dahu attitude toward students is not only the Pancasila and civic education teacher’s responsibility, but it needs the involvement of all school sides to conduct supervision, assistance, family environment, community and government. Third, the form of practicing the values of Pancasila in MTsN I Bima city, including: first principle, divine value (learning to read Al-Qur'an, hadith, praying in congregation, lecturing and reading yasin). the second principle, the value of humanity (tolerance, help, kinship, and mutual respect). third principle, the value of unity (raising the red and white flag, commemorating the Proclamation Day of August 17, reforestation, and loving local culture). The fourth principle, the value of populist (deliberation and consensus, the selection of class chairmen, student council chairmen, scout leaders and harvest discussions). And the fifth principle, the value of justice (sense of brotherhood, solidarity, tolerance and help).